Aquatic macroinvertebrates inhabiting the roots of water hyacinth (Eichhornia crassipes Mart.)in Lake Mihaba, Bunawan, Agusan del Sur - Abreo, Neil Angelo S. (2007)
This study was done to determine the diversity of macroinvertebrate inhabiting the roots of water hyacinth (Eicchornia crassipes) in Lake Mihaba, Agusan del Sur. Roots were taken from the site using a 25 x 30 cm. scoop net during the months of May, October and December 2004 and February 2005 for seasonal variation. The roots were sieved using 1 and 0.5 mm mesh wire to obtain the desired invertebrates. Thirty-three categories were identified (n=7475) which was primarily dominated by order Diptera (49.43%), Decapoda (17.30%) and Ephemeroptera (12.62%). Generally, macroinvertebrates in Lake Mihaba is diverse (H? =0.86) but not evenly distributed (J?=0.56) hence the domination of families Chironomidae (41.24%), Atyidae (17.30%), Culicidae (7.48%) and Dysticidae (5.61% was observed. Results of the analysis of variance (ANOVA) nullify the differences of diversity mean across seasons and across all sites. No significant correlation is observed with water depth and water temperature to the diversity of correlation is observed with water depth and water temperature to the diversity of macroinvertebrates. Meanwhile, root mass slightly affects (2.192.042 at =0.05) the diversity of macroinvertebrates inversely
Thesis (BS Biology) -- University of the Philippines Mindanao, 2007
Keywords: Macroinvertebrates; Macroinvertebrates -- Diversity; Water hyacinth; Lake Mihaba -- Bunawan, Agusan del Sur -- Philippines; Analysis of variance (ANOVA)